Lung cancer related to environmental and occupational hazards and epidemiology in Chiang Mai, Thailand - Wiwatanadate P. (2014)
The causes of lung cancer in northern Thailand have not been completely understood, but it is strongly believed that they are multi-factorial. The environmental and occupational factors have played a significant role on lung cancer. They can be categorized as physical, chemical, and biological. In the northern region of Thailand, specifi- cally Chiang Mai province, it has been recognized that the incidence of lung cancer is among the highest in Thailand. For example, in the year 2007, the age-standardized incidence rate in males was 31.3 and that in female was 22.9 per 100,000 population. The district ranked the highest was Muang district, Chiang Mai. The previous studies showed that, apart from smoking, the indoor radon, air pollution and genetic factors might be the causes. © The Japanese Environmental Mutagen Society.